- The Implementation Of Digital Branding with Search Engine Optimization Technique Used Web Based: - - EKATRI AYUNINGSIH; Sri Eka Wulandari; Alexander Robintang Gurning (Bahasa Indonesia, 2023)
The advance of information technology and the strick business competition require every business to implement the right product marketing strategies to gain a competitive edge. PT Reksa Nusindo Sejahtera, a company specializing in medical and diagnostic laboratory equipment distribution located in Medan, is no exception. PT Reksa Nusindo Sejahtera currently needs to build its corporate image among the community or market. This phenomenon has driven the author to conduct research on digital branding for PT Reksa Nusindo Sejahtera. In the process of implementing digital branding through a website in the research, the author implemented search engine optimization technique. The objective of this research is to create a website that applied search engine optimization techniques to enhance search engine result page rangkings, in order to appear on the first page of Google Search Result within more than 6 months. It is expected to increase the branding of PT Reksa Nusindo Sejahtera. The research results indicate that digital branding is highly effective in establishing the enterprise’s image and increasing website traffic, ultimately leading to higher sales.